(untitled) (Contemporary Mathematics, 2025)
In current network systems, cryptography plays a vital role in ensuring a secure data transfer. Robust encryption is essential to safeguard data during transmission, making it a top priority. Encryption transforms readable data into an unreadable format and is commonly used for data protection. Modern cryptography incorporates graph theory principles to enhance the security of information-sharing over networks. This study introduces an ASCII-based data encryption system that utilizes a Coloring Tripartite Graph (CTG) as a confidential key to facilitate secure data exchange. In addition to detailing the security protocols, the recipient receives encrypted data in the form of CTG. The adoption of this encryption technology significantly enhances the security of data transmissions.